Curcumin-mediated Photodynamic Therapy Inhibits the Phenotypic Transformation, Migration, and Foaming of Oxidized Low-density Lipoprotein-treated Vascular Smooth Muscle Cells by Promoting Autophagy. Issue 2 (August 2021) - Wang, Gailan; Zhu, Ying; Li, Kaiting; Liao, Bo; Wang, Fang; Shao, Lan; Huang, Liyi; Bai, Dingqun
Abstract : Abstract: Vascular smooth muscle cells (VSMCs) are becoming a hot spot and target of atherosclerosis research. This study aimed to observe the specific effects of curcumin (CUR)-mediated photodynamic therapy (CUR-PDT) on oxidized low-density lipoprotein (ox-LDL)-treated VSMCs and confirm whether these effects are mediated by autophagy. In this study, the mouse aortic smooth muscle cell line and A7r5 cell lines were used for parallel experiments. VSMC viability was evaluated by Cell Counting Kit-8 assay. VSMCs were treated with ox-LDL to establish a model of atherosclerosis in vitro. The autophagy level and the expression of proteins related to phenotypic transformation were detected by western blotting. The migration ability of the cells was detected by using transwell assay. The presence of intracellular lipid droplets was detected by Oil Red O staining. The results showed that VSMCs transformed from the contraction phenotype to the synthetic phenotype when stimulated by ox-LDL, during which autophagy was inhibited. However, CUR-PDT treatment significantly promoted the level of autophagy and inhibited the process of phenotypic transformation induced by ox-LDL. In addition, ox-LDL significantly promoted VSMC migration and increased the number of lipid droplets, whereas CUR-PDT treatment significantly reduced the ox-LDL-induced increase in the migration ability of, and lipid droplet numbers in, VSMCs. When the VSMCs were pretreated with the autophagy inhibitor 3-methyladenine for 24 hours, the effects of CUR-PDT were reversed. Therefore, our study indicated that CUR-PDT can inhibit the phenotypic transformation, migration, and foaming of ox-LDL–treated VSMCs by inducing autophagy. Abstract : Supplemental Digital Content is Available in the Text.